Plasmid profile analysis of Portuguese Borrelia lusitaniae strains - Vitorino, Liliana (2011)
Plasmid profilesof2Portuguese Borrelia lusitaniae strains, oneisolatedfromahumanpatientandthe other onefroman Ixodes ricinus tick, wereobtainedbypulsed-fieldgelelectrophoresistoevaluatethe plasmid diversityineachstrain.Overall,amaximumof6plasmidsweredetectedthatrangedfrom 19 kbto76kb,revealingcompletelydifferentplasmidprofilesfromthosepreviouslydescribedforother genospecies of B. burgdorferi sensu lato,thecausativeagentsofLymeborreliosis.Theplasmidlocationof the ospA gene wasinvestigatedbyhybridization,allowingitsallocationtotheplasmidof70kbinstead of the54kblinearplasmiddescribedfor B. burgdorferi sensu strictostrains.